Wie mobil ist Kapital? Empirische Evidenz für Deutschland - Susanne Lapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
– The extent of capital mobility between the Bundesländer of West-Germany between 1975-1990 is investigated. The investigation is based on the approach first chosen by Feldstein and Horioka who estimated the correlation between national saving and Investment rates. It is shown that the correlation of regional saving and Investment rates in Germany decreased substantially over time reflecting an increase in capital mobility. Furthermore, it is found that the government influences the correlation between saving and investment. Whereas in the time period 1975-1982 the correlation for the economy as a whole was higher than for the private sector, the opposite result is obtained for the period 1983-1990. A possible explanation could be the shift frorn a supply to a demand side policy that occured during the period under consideration.
Keywords: E44; 330; Kapitalmobilität; Sparen; Investition; Deutschland